The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1007/s10995-018-2537-7
|View full text |Cite|
|
Sign up to set email alerts
|

Randomized Controlled Trial of Doula-Home-Visiting Services: Impact on Maternal and Infant Health

Abstract: Introduction Although home-visiting programs typically engage families during pregnancy, few studies have examined maternal and child health outcomes during the antenatal and newborn period and fewer have demonstrated intervention impacts. Illinois has developed an innovative model in which programs utilizing evidence-based home-visiting models incorporate community doulas who focus on childbirth education, breastfeeding, pregnancy health, and newborn care. This randomized controlled trial (RCT) examines the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
112
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(122 citation statements)
references
References 28 publications
2
112
0
2
Order By: Relevance
“…The model has been described in a variety of sources, including a book (Abramson, Isaacs, & Breedlove, ) and a documentary film (Alpert & Suffredin, ). Randomized controlled trials of the community doula model have shown positive impacts of the intervention on breast‐feeding as well as early mother–infant interaction (Edwards et al., ; Hans, Edwards, & Zhang, ; Hans et al., ).…”
Section: Reproductive Justice Within Two Infant Mental Health Programsmentioning
confidence: 99%
“…The model has been described in a variety of sources, including a book (Abramson, Isaacs, & Breedlove, ) and a documentary film (Alpert & Suffredin, ). Randomized controlled trials of the community doula model have shown positive impacts of the intervention on breast‐feeding as well as early mother–infant interaction (Edwards et al., ; Hans, Edwards, & Zhang, ; Hans et al., ).…”
Section: Reproductive Justice Within Two Infant Mental Health Programsmentioning
confidence: 99%
“…Personal vulnerability was usually in the form of low family income [32][33][34][35][36][37], even though only one of the studies reported recruitment based on an absolute income limit, defined as 200% of federal poverty level [37]. Another type of personal vulnerability was social risk, which included several types of socioeconomic and interpersonal risk factors.…”
Section: Personal Vulnerabilitymentioning
confidence: 99%
“…Recruitment by disadvantaged socioeconomic groups were based on ethnicity [32][33][34][35][40][41][42][43] and age [32][33][34][35]42]. The ethnic minority groups in question were Hispanics [40,41,43], Koreans [40], Native Americans [42] and African Americans [32][33][34][35]. McLeish and Redshaw used HIV diagnosis rather than ethnicity as a basis for recruitment, but the large majority of their participants were immigrant women with a Sub-Saharan African background [44].…”
Section: Demographic Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the potential benefits of CHW intervention, there is a paucity of research on how CHWs can help pregnant women with chronic conditions have healthier pregnancies, with much of the research in this area focusing exclusively on doula support. Several states have expanded Medicaid coverage for doula services [19][20][21] based on research documenting benefits of continuous labor care for pregnant and postpartum women [22,23]. Although doulas and CHWs both provide support to women during pregnancy, doula services are typically confined to active labor and the immediate postpartum period [24].…”
Section: Introductionmentioning
confidence: 99%